Drug utilization pattern in type II diabetes mellitus patients attending non-communicable disease clinic in a tertiary care hospital - Gadgade, Akash; B., Shwetha; Kotinatiot, Basavaraj C.; C., Chetan A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes mellitus is a metabolic disorder. Early institution of treatment is necessary to prevent complications. Since treatment of diabetes requires lifetime therapy; this study is designed to understand the prescription trends at Non Communicable Disease clinic set up and to provide rationale. Methods: This cross-sectional, observational study was conducted over a period of 2 months (May 2017- June 2017). Details of demographic data, duration and family history of diabetes, antidiabetic medications prescribed, history of comorbid diseases and drugs prescribed by physician for the treatment of comorbid diseases were collected in a structured format. Height and weight were recorded, and body mass index was calculated. Results: Study population included 294 patients and patients in the age groups of 40-59 years formed the bulk. 39% patients were overweight and 19.39% were obese. 93.20% patients were prescribed with metformin. 37 patients received insulin injection. 64.29% received more than one antidiabetic drug. Hypertension (82.05%) was the most common comorbid disease. Amlodipine was the most commonly prescribed antihypertensive drug. Conclusions: Metformin was the most commonly prescribed antidiabetic drug. Utilization of newer antidiabetic drug is inferior. Use of rationale fixed dose combination improves patient compliance.